Clinical Characteristics and Survival in Patients with Brain Metastases From Pancreatic Cancer: A Retrospective Observational Study - Susan Haag PhD; Derek Cridebring PhD (Cancer Control)
Introduction Brain metastasis (BM) is an inauspicious finding in patients with pancreatic cancer, which significantly increases morbidity and mortality. The presentation is rare, and thus, outcomes on brain metastases from pancreatic cancer are limited. Methods This retrospective monocentric analysis included the electronic medical records of patients ≥ 18 years presenting with BM from pancreatic cancer. Clinical, demographic, and overall survival (OS) data were analyzed. Brain imaging (computed tomography, and magnetic resonance imaging) was used for BM diagnosis. OS was calculated from the date of diagnosis to either the date of last follow-up or death. Cox regression on OS time was used with an indicator variable for patients who ultimately developed a BM. Results Brain metastases was diagnosed in 34 (3.7%) patients with pancreatic cancer treated in our institution. Of the BM patients: 7 (22%) were non-White; 16 (47%) were female; the median age was 69; 35% were diagnosed at Stage II and III; and 65% were diagnosed at Stage IV. BM was the first diagnosed metastasis in 14 (41%) of the patients; in 5 individuals (15%) BM were detected within the first 100 days of pancreatic cancer diagnosis. OS from BM diagnosis was 9 months (95% CI [6.92,17.86]). The adjusted hazard ratio for patients with BM was .91(95% CI [.88, .94]; P = 0.60], which was not significant. Conclusions Due to the low incidence of BM in pancreatic cancer, identification of disease remains a current challenge. In this study, we found that BM from pancreatic cancer may be the first sign that the cancer has spread. Using advanced neuroimaging early may help physicians diagnose these metastases sooner and possibly improve survival. With a larger cohort size, the findings may be potentially impactful for clinicians and patients. Prospective, multicentric studies are warranted to identify prognostic factors for treatment and survival.